A cluster Analysis for Binary Data Using Genetic Algorithms - Saharan, Sabariah; Yu Xian, Wong; Baragona, Roberto (International Journal of Engineering and Technology, 2018)
This research was initially driven by the lack of clustering algorithms that focus on binary data. A promising technique to analyze this type of data, namely Genetic Clustering for Unknown K (GCUK) became the main subject in this research. GCUK was applied to cluster four binary data and there is a presence of an imbalanced data in one of the data sets. The results show that GCUK is an efficient and effective clustering algorithm compared to K-means. The other contribution is the capability of GCUK for clustering the unbalanced data. Standard clustering algorithms cannot simply be applied to this type of data sets as it can cause a misclassification results.Â